Family systems and obesity: A review of key concepts and influences within and between family subsystems and a call for family‐informed interventions. Issue 1 (9th September 2022) - Novak, Josh R.; Pratt, Keeley; Hernandez, Daphne C.; Berge, Jerica M.
Abstract: Research on the social determinants of obesity describes the importance of family dynamics and how they can influence an individual's weight and weight‐related behaviors. These proximal influences include parent–child, couple, and limited research on intergenerational and sibling dynamics. However, familial research is often isolated to one relationship subsystem (i.e., parent–child or couple) and is not integrated into the larger Family Systems Theory (FST) framework. The purpose of this paper is twofold: to present recommendations for future work by expounding on FST concepts for weight management and obesity prevention, and to provide a review of the theoretical and empirical evidence for each family system and subsystem, including (a) the extended family, (b) family environment, (c) couple, (d) parent–child, and (e) sibling, and present methodological and analytical considerations.